Sexual attitudes and utilization of sexual and reproductive health services among older women in southern China: a qualitative study - Peng, Xin; Wang, Bingyi; Wang, Qianyun; Li, Yuwei; Sun, Yinghui; Li, Xinyi; Tucker, Joseph D.; He, Longtao; Tang, Weiming; Wu, Dan; Zou, Huachun (Frontiers in Public Health, 2024)
Objective: Sexual health plays a vital role in healthy aging. However, little is known about the sexual attitudes of and the utilization of sexual and reproductive health services by older women in China. This article is based on a qualitative study of older Chinese women in suburban areas to examine their attitudes toward sexuality and their utilization of sexual and reproductive health services. Methods: Face-to-face semi-structured interviews were conducted with older women (ages 50 to 74) from suburbs of southern China. Participants were purposively sampled on a convenience basis and recruited when they were visiting community health facilities between June and December 2021. Inclusion criteria were older women aged 50 years and older who had sexual experience. A topic guide was used that focused on sexual activity, sexual attitudes, the utilization of sexual and reproductive health services, and the factors that influence these. Interviews were audio recorded and transcribed verbatim. We coded the data inductively and conducted a thematic analysis. Results: Twenty-six Chinese women participated in the study. These older women had varying attitudes regarding sexual activity and its significance for older adults. The gender norms they held concerning sexual desire deemed that men had higher sexual desire than women. Most asymptomatic women did not actively seek sexual and reproductive health services. In most cases, women only sought professional services when they started to have sexual and reproductive health problems. Factors influencing the uptake of sexual and reproductive health services by older women were cost (affordability), availability, distance (accessibility), and conservative cultural norms towards sexuality. Conclusion: The attitudes of older women towards sexual activity are diverse. While some view sexual activity as common and essential for maintaining a sense of well-being in older age, others may hold different perspectives, considering it less significant. The utilization of sexual and reproductive health services by older Chinese women, except for when they were having a specific health issue, was low. Sexual health messages and services tailored for older women are needed.